DEVELOPMENT OF LEARNING MEDIA WITH SMART APPLICATIONS APPS CREATOR IN COMPUTER SYSTEM SUBJECTS IN VOCATIONAL HIGH SCHOOLS MIFTAHASA'ADAH CIKANDE - Sarmila; Basrowi; Kurniati Rahmadani (Cakrawala Pedagogik, 2023)
Educational activities are efforts to develop good and competent individuals to improve living standards, technological sophistication has an impact and an important role in educating the nation's children. Therefore researchers utilize Android-based technology for interesting learning media, namely using the Smart Apps Creator. This researcher uses the  ADDIE model, namely: analysis, design, development, implementation and evaluation. The ADDIE development model is to see the feasibility of Smart Apps Creator Learning Media. Data on the practicality of Smart Apps Creator Learning as a learning resource through a practicalization trial of 32 students at the Miftahusa'adah Cikande Vocational School with a total of 18 question points seen an average value of 81.34%, it can be said that the practicality level of Smart Apps Creator learning is Practical. Data on the effectiveness of Smart Apps Creator Learning Media as a learning resource through a trial of the effectiveness of 32 students with a total of 12 question points seen an average value of 83.05%, it can be said that the level of effectiveness of Smart Apps Creator Learning Media is stated to be Effective